2018
DOI: 10.1111/nph.15525
|View full text |Cite
|
Sign up to set email alerts
|

Retrograde signalling as an informant of circadian timing

Abstract: Contents Summary1749I.The circadian system is responsive to environmental change1749II.Photoassimilates regulate circadian timing1750III.Retrograde signals contribute to circadian timing1750IV.Conclusions1752Acknowledgements1752References1752 Summary The circadian system comprises interlocking transcriptional–translational feedback loops that regulate gene expression and consequently modulate plant development and physiology. In order to maximize utility, the circadian system is entrained by changes in tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…This can be explained by the photoprotective mechanism of non-photochemical quenching, that allows for the sequestration of reactive oxygen species (ROS) below critical levels [61]. Otherwise, an increase in ROS triggers remarkable damage to the metabolic machinery, inducing photoinhibition and a generalized damage response [67,68,69].…”
Section: Discussionmentioning
confidence: 99%
“…This can be explained by the photoprotective mechanism of non-photochemical quenching, that allows for the sequestration of reactive oxygen species (ROS) below critical levels [61]. Otherwise, an increase in ROS triggers remarkable damage to the metabolic machinery, inducing photoinhibition and a generalized damage response [67,68,69].…”
Section: Discussionmentioning
confidence: 99%
“…Two other subunits of magnesium chelatase are encoded by genes that were identified in Arabidopsis as genomes uncoupled mutants, gun4 and gun5, with altered retrograde, plastid-to-nuclear, signaling with defects in chlorophyll metabolism (Susek et al 1993;Mochizuki et al 2001;Larkin et al 2003). Multiple studies have demonstrated retrograde signaling mutants with defects in chlorophyll metabolism (Hernández-Verdeja and Strand 2018) and circadian rhythm (Jones 2019). Retrograde signaling events are also associated with cell death, chloroplast development, and etiolation but it acts via a number of modifiers of flowering, including phytochromes, phytochrome signaling components, blue light perception via crytochrome1, and circadian rhythmicity of key genes that affect flowering time.…”
mentioning
confidence: 99%
“…The redox state of the PQ pool is of unique significance for antioxidant defense and signaling [65]. It has been shown recently that ROS generation is influenced also by the circadian system [66,67]. We postulate that ROS generation at 30 min after the NPs spray (Figure 11b) possibly served as the signaling molecule to contribute to a more oxidized state of the PQ pool at 90 min after the NPs spray (Figure 6, Figure 9c), resulting in a H 2 O 2 production similar to the control leaf level (Figure 11c).…”
Section: Discussionmentioning
confidence: 99%